The influence of hydraulic prosthetic ankle on walking of a person after bilateral transtibial amputation - Cergol, Sergeja (Rehabilitacija (Ljubljana), 2022)
Background: Several articles about hydraulic ankles can be found in the PubMed bibliographic database, but we did not find any study about the influence of passive hydraulic ankle on walking upand downhill in persons after bilateral transtibial amputation. The aim of our study was to assess this influence in a person after bilateral transtibial amputation. Methods: The subject in our study was a 50-years old woman after bilateral transtibial amputation performed five years before the study due to complications of type I diabetes. Most measurements were performed three times – on the admission day with the patient’s previous prostheses, after two weeks of training with the new prostheses with hydraulic prosthetic feet, and three months after discharge. We performed a structured interview, clinical tests, patient-reported outcome measures (PROMs) and kinesiological measurements during walking on flat, up- and downhill surfaces. Results: While the patient reported subjective improvement on all questions of the structured interview and PROMs, we did not detect any objective improvement with clinical tests and only very small, probably clinically not important differences with kinesiological measurements. Conclusions: Clinical tests and kinesiologic measurements did not confirm the subjective improvement felt by the patient. It is not possible to generalise our results to other subjects after bilateral transtibial amputation.
Keywords: Amputation; bilateral transtibial amputation; Gait; hoja navzdol; obojestranska transtibialna amputacija; pasivno hidravlično protezno stopalo; passive hydraulic prosthetic ankle; Prostheses and Implants; rehabilitation; walking downhill